Modulation frequency constraints on wow and flutter determination - MAZIEWSKI, Przemysław (Archives of Acoustics, 2008)
Hitherto developed algorithms for wow and flutter characteristic determination were found useful in some real-life restoration procedures, however, there was no study of their capabilities in terms of the maximal parasite modulation frequency that can be determined with their application. This paper presents the study for three algorithms, i.e. the power-line hum tracker, high frequency bias tracker, and the center of gravity tracker. The short description of the algorithms is followed by the theoretical study on the maximal modulation frequency determined by the algorithms. Next, the experimental part is given, with simulations which confirm the findings from the theoretical part, and conclusions summarizing obtained results.